Optimised diamond to graphite conversion via a metastable sp1-bonded carbon chain formation under an ultra-short femtosecond (30 fs) laser irradiation. (February 2023) - Ali, Bakhtiar; Xu, Han; Sang, Robert T.; Litvinyuk, Igor V.; Rybachuk, Maksym
Abstract: An application of an ultra-short femto-second ( fs ) pulsed laser (30 fs, 800 nm, 1 kHz) radiation under a simultaneously varied laser fluence (0.6, 1.2 and 1.8 J/cm 2 ) and number of pulses (2000–32, 000 pulses per irradiation site) to process diamond has been investigated to determine an optimal conversion of the diamond's tetrahedral sp 3 phase into an aromatic sp 2 phase with a high degree of crystallinity and without a formation of an sp 2 olefinic fraction, thermal damage or an irradiation-induced surface cracking. The highest sp 2 aromatic crystallinity and the most significant sp 3 -to- sp 2 conversion efficiency in diamond was attained at 1.2 J/cm 2 with 32, 000 pulses. The sp 3 -to- sp 2 phase transition was marked by a formation of a metastable carbon in the sp 1 hybridisation ( carbyne ), evidenced by the characteristic Raman mode at ca. 2065 cm −1 . Inclusions of covalently bound carbonyl (-CO) at ca. 1705 cm −1 were also observed on diamond under lower irradiation doses. Both the sp 1 and carbonyl contributions resolved gradually as irradiation dose increased. Well-defined laser-induced periodic surface structures (LIPSS) ( aka . nano-ripples) with a high spatial frequency distribution and periodicity of around 100 nm were observed forming in the irradiated regions on diamond owing to the interaction of the laser pulse with the surface plasmons; an ordered and homogeneous formation of LIPSS structures has been observed at 1.2 J/cm 2 with 8000 pulses. The impact and implications of these findings on the design and development of future ' all-carbon ' devices by means of a direct non-ablative fs laser processing of diamond are discussed. Graphical abstract: Image 1